Pengembangan Sistem Aplikasi Antrian Pelayanan Daring Berbasis Website Studi Kasus: Kelurahan Pejuang Bekasi - Najib Hamala Sidri; Harya Bima Dirgantara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to build an online service queuing system application in Kelurahan Pejuang Bekasi that can run on the Website. This queuing system application can be used by residents of Kelurahan Pejuang Bekasi who want to provide services without the need to visit the location by simply uploading the selected service requirements document. The system development method used is the Rational Unified Process (RUP) and the modeling used is the Unified Modeling Language (UML). Develop this application using Sublime Text as a code editor with the php programming language, javascript for modeling application creation and codeigniter as a framework. The results obtained in this study are the application runs on a website-based system to perform services without the need to visit the location by simply uploading the selected service requirements document.